The public health laboratories in health programmes - Carvalho, João Pessoa de Paula (Revista de Saúde Pública, 1976)
The public health laboratories are closely connected to every modern programme of medical care and public health. Problems concerning the demand of services and the means to satisfy them derive from the mentioned relationship. Throughout this paper the need for greater understanding of laboratory service importance is shown and discussed along with its trends. Technological progress and some basic elements must be considered when planning and organizing a national public health integrated laboratory system.